Kualitas Komunikasi Keluarga tenaga kesehatan dimasa Pandemic Covid-19 - Nursanti, Siti; Utamidewi, Wahyu; Tayo, Yanti (Jurnal Studi Komunikasi, 2021)
This study aims to determine the motives of health workers who are still carrying out their profession during the COVID-19 pandemic and how the quality of health family communication during the COVID-19 pandemic. This research uses descriptive qualitative research method by collecting interview data online through zoom. The results of this study indicate that there is a motive for health workers who are still carrying out their profession during the COVID-19 pandemic, it is part of the profession that must be carried out because from the beginning they chose to work as health workers and during the COVID-19 pandemic if health workers did not carry out their obligations seriously. then this pandemic will never end. Communication barriers that occur due to difficulties in meeting with family members are replaced by the presence of communication technology. This even affects the quality of communication in the form of closeness and support among family members.